Comparative genomic analysis of Genlisea (corkscrew plants—Lentibulariaceae) chloroplast genomes reveals an increasing loss of the ndh genes - Silva, Saura R. [UNESP]; Michael, Todd P.; Meer, Elliott J.; Pinheiro, Daniel G. [UNESP]; Varani, Alessandro M. [UNESP]; Miranda, Vitor F. O. [UNESP] (Public Library of Science (PLoS), 2018)
In the carnivorous plant family Lentibulariaceae, all three genome compartments (nuclear, chloroplast, and mitochondria) have some of the highest rates of nucleotide substitutions across angiosperms. While the genera Genlisea and Utricularia have the smallest known flowering plant nuclear genomes, the chloroplast genomes (cpDNA) are mostly structurally conserved except for deletion and/or pseudogenization of the NAD(P)H-dehydrogenase complex (ndh) genes known to be involved in stress conditions of low light or CO2 concentrations. In order to determine how the cpDNA are changing, and to better understand the evolutionary history within the Genlisea genus, we sequenced, assembled and analyzed complete cpDNA from six species (G. aurea, G. filiformis, G. pygmaea, G. repens, G. tuberosa and G. violacea) together with the publicly available G. margaretae cpDNA. In general, the cpDNA structure among the analyzed Genlisea species is highly similar. However, we found that the plastidial ndh genes underwent a progressive process of degradation similar to the other terrestrial Lentibulariaceae cpDNA analyzed to date, but in contrast to the aquatic species. Contrary to current thinking that the terrestrial environment is a more stressful environment and thus requiring the ndh genes, we provide evidence that in the Lentibulariaceae the terrestrial forms have progressive loss while the aquatic forms have the eleven plastidial ndh genes intact. Therefore, the Lentibulariaceae system provides an important opportunity to understand the evolutionary forces that govern the transition to an aquatic environment and may provide insight into how plants manage water stress at a genome scale.